2019
DOI: 10.1249/mss.0000000000001988
|View full text |Cite
|
Sign up to set email alerts
|

Overactivation of the Reward System and Deficient Inhibition in Exercise Addiction

Abstract: Purpose Behavior studies have found that exercise addiction is associated with high impulsivity. In other addictions, neural mechanisms of impulsivity reflect abnormalities in the reward and inhibition systems. In this study, we determined whether abnormalities existed in the reward and inhibition systems of exercise addicts. Methods Three groups of male participants (15 exercise addicts, 18 regular exercisers, and 16 exercise avoiders) completed the Mini International … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
(53 reference statements)
2
13
0
Order By: Relevance
“…Although the current findings are based on a cross-sectional design, which is inappropriate for establishing any casual relationships, we assume that an increased risk of exercise addiction might be a result of the interface between psychological distress and emotional dysregulation. Our findings and proposition are in line with some current neurophysiological results using cognitive tasks (Huang et al, 2019). Using Go/No-go tasks in regular exercisers, exercise addicts, and exercise avoiders, the authors confirmed an overactivation of the reward system of the individuals in the exerciser groups.…”
Section: Discussionsupporting
confidence: 93%
“…Although the current findings are based on a cross-sectional design, which is inappropriate for establishing any casual relationships, we assume that an increased risk of exercise addiction might be a result of the interface between psychological distress and emotional dysregulation. Our findings and proposition are in line with some current neurophysiological results using cognitive tasks (Huang et al, 2019). Using Go/No-go tasks in regular exercisers, exercise addicts, and exercise avoiders, the authors confirmed an overactivation of the reward system of the individuals in the exerciser groups.…”
Section: Discussionsupporting
confidence: 93%
“…Abnormalities in reward and inhibition systems are found in exercise addicts, which may explain their impulsivity, loss of control, and interference in decisionmaking. In addicts' brains, reward system overactivation is revealed by enhanced activities in the prefrontal, limbic, and striatal areas, while an impaired inhibition system is reflected by lower N2 and P3 amplitudes in the orbitofrontal-dorsolateral cortices (Huang et al, 2019). These individuals have to exercise more to trigger chemical release which describes reward-seeking behaviour.…”
Section: Exercise Addiction and Covid-19-associated Restrictionsmentioning
confidence: 99%
“…It seems reasonable to assume these characteristics may contribute to the development of exercise addiction. In addition, narcissistic vulnerability is similar to the basic personality dimensions of neuroticism [ 64 ] which has been found to be associated with exercise addiction [ 15 , 25 , 65 , 66 ].…”
Section: Introductionmentioning
confidence: 99%